THE INFLUENCE OF INNOVATIVE WORK ON EMPLOYEE PERFORMANCE WITH PARTICIPATIVE LEADERSHIP STYLE AS A MODERATING VARIABLE - Rahmat Rahmat; Faizal Faizal; Raihan A. Hanasi; Lulu Ulfa Sholihannisa; Nurmahadi Nurmahadi (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This research is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies, namely as the main support for building the foundation of the research being conducted. The data used in this article are primary data that researchers obtained from Muhammadiyah Hospitals spread throughout Indonesia as many as Five Hundred people. The data were collected through an online questionnaire containing 5 statements: strongly agree, agree, normal/so-so, disagree, and strongly disagree. The data used were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Work Innovation variable can have a positive relationship direction and a significant influence on Employee Performance because the P-Values are positive and below the significance level of 0.05, namely 0.003. In line with the first hypothesis above, the next row also shows results that are in line with the hypothesis proposed by the researcher, namely that the Participative Leadership variable can strengthen the influence of the Work Innovation variable on Employee Performance because the P-Values are positive and below the significance level of 0.05, namely 0.000. This is because participatory leadership can increase employee motivation and enthusiasm in working, making employees more innovative and their performance also increases. Keywords: Innovative Work, Employee Performance, Participative Leadership Style